2015
DOI: 10.1016/j.stemcr.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Lumen Formation Is an Intrinsic Property of Isolated Human Pluripotent Stem Cells

Abstract: SummaryWe demonstrate that dissociated human pluripotent stem cells (PSCs) are intrinsically programmed to form lumens. PSCs form two-cell cysts with a shared apical domain within 20 hr of plating; these cysts collapse to form monolayers after 5 days. Expression of pluripotency markers is maintained throughout this time. In two-cell cysts, an apical domain, marked by EZRIN and atypical PKCζ, is surrounded by apically targeted organelles (early endosomes and Golgi). Molecularly, actin polymerization, regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
99
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 24 publications
12
99
0
1
Order By: Relevance
“…Studies in diverse vertebrate cell types in vitro and in vivo demonstrate a key role for formins in coordinating apical surface formation among groups of cells during epithelial lumen formation (Grikscheit et al, 2015;Madrid et al, 2010;Phng et al, 2015;Taniguchi et al, 2015). Likewise, our data here and in previous work (Sedzinski et al, 2016) demonstrate a similar requirement for formins in the emergence of an individual apical epithelial surface in MCCs.…”
Section: Discussionsupporting
confidence: 85%
“…Studies in diverse vertebrate cell types in vitro and in vivo demonstrate a key role for formins in coordinating apical surface formation among groups of cells during epithelial lumen formation (Grikscheit et al, 2015;Madrid et al, 2010;Phng et al, 2015;Taniguchi et al, 2015). Likewise, our data here and in previous work (Sedzinski et al, 2016) demonstrate a similar requirement for formins in the emergence of an individual apical epithelial surface in MCCs.…”
Section: Discussionsupporting
confidence: 85%
“…For example, by embedding dissociated hESCs into a gel of ECM proteins it was shown that hESCs spontaneously form a lumen (Fig. 2C) due to interactions with the ECM (Bedzhov and ZernickaGoetz, 2014;Kadoshima et al, 2013;Taniguchi et al, 2015), in the same way as shown previously for Madin-Darby canine kidney (MDCK) and human colorectal cancer cells, both of which are common models of epithelia (Martin-Belmonte and Mostov, 2008;Rodriguez-Fraticelli and Martin-Belmonte, 2013). In the case of developing MDCK cysts, actin-associating proteins such as ezrin are trafficked to the cytokinetic plane as single cells first divide (Bryant et al, 2014), forming an actin-rich site and marking the initiation region for the apical membrane (Apodaca et al, 2012).…”
Section: Factors That Regulate Cavitation and Lumenizationsupporting
confidence: 64%
“…Cells then self-organize into an epithelium, forming a lumen at their apical sides. Apparently, in the case of dissociated human pluripotent stem cells, the lumen can already be seen after the first division between two cells in 3D culture (Taniguchi et al, 2015). By modifying the 3D culture medium, it has also been shown that human pluripotent stem cells can differentiate into amnion-like cells surrounding a lumen at the center of the colony (Shao et al, 2016).…”
Section: Factors That Regulate Cavitation and Lumenizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other in vitro models have demonstrated some degree of self-organization when human embryonic stem cells are cultured in 3D environments 10 .…”
Section: Two Goalsmentioning
confidence: 99%